2016
DOI: 10.3390/s16091546
|View full text |Cite
|
Sign up to set email alerts
|

Features of a Self-Mixing Laser Diode Operating Near Relaxation Oscillation

Abstract: When a fraction of the light reflected by an external cavity re-enters the laser cavity, both the amplitude and the frequency of the lasing field can be modulated. This phenomenon is called the self-mixing effect (SME). A self-mixing laser diode (SM-LD) is a sensor using the SME. Usually, such LDs operate below the stability boundary where no relaxation oscillation happens. The boundary is determined by the operation condition including the injection current, optical feedback strength and external cavity lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In stable region, for a stationary target, the laser intensity will be constant after the transient state, whereas in semi-stable and unstable region, relaxation oscillation will be undamped and the laser may enter period-one, quasiperiodic or chaotic oscillation under different feedback strength. The work [21,22] discovers that an OFLD can easily and sometimes inevitably enter the period-one oscillation, e.g. for the case when the feedback level factor C is around 2.5, which is quite commonly reported for the moderate feedback regime in the literature.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In stable region, for a stationary target, the laser intensity will be constant after the transient state, whereas in semi-stable and unstable region, relaxation oscillation will be undamped and the laser may enter period-one, quasiperiodic or chaotic oscillation under different feedback strength. The work [21,22] discovers that an OFLD can easily and sometimes inevitably enter the period-one oscillation, e.g. for the case when the feedback level factor C is around 2.5, which is quite commonly reported for the moderate feedback regime in the literature.…”
Section: Introductionmentioning
confidence: 88%
“…However, many works [18][19][20] have demonstrated that an OFLD system with a stationary external target may be unstable under some certain operation conditions, such as in periodic, quasi-periodic or chaotic oscillation state. We studied OFLD signals with a moving target in different conditions and our recent works [21,22] shows that such sensing system may produce different types of OFLD signals which are classified into three regions defined in [21], i.e. stable, semi-stable and unstable region under different feedback level factors C. C is defined as:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that damped oscillation appears on the discontinuous point of the SMI signal when the SMLD system operates in moderate feedback regime and this kind of damped oscillation corresponds to the external cavity mode, which contains information on the target distance and reflectivity. Additionally, our recent work [17,18] shows another kind of oscillation, i.e. undamped relaxation oscillation (RO), may occur when the SMLD operates in moderate or strong feedback regime.…”
Section: Pd Ldmentioning
confidence: 99%